Pre- and intraoperative variables affecting early outcomes in elderly patients undergoing pancreaticoduodenectomy - de la Fuente, Sebastian G (Blackwell Publishing Ltd, 2011)
BACKGROUND: Conflicting data exist regarding the safety of pancreatic resections in elderly patients. In this study we compared early complication and mortality rates between patients younger and older than 80 years of age who underwent pancreaticoduodenectomy using a validated national database. METHODS: The National Surgical Quality Improvement Program (NSQIP) database for 2005–2009 was used for this retrospective analysis. The primary outcome measures for our analysis were 30-day postoperative mortality, major complication rate and overall complication rate. RESULTS: A total of 6293 patients who underwent PD for any cause were included in the analysis. Of these, 9.4% were aged ≥80 years. The incidence of 30-day mortality was significantly higher in patients aged ≥80 years (6.3%) than in those aged <80 years (2.7%). Older patients were also noted to have higher rates of overall complications and serious complications. On multivariate analysis, age, ASA (American Society of Anesthesiologists) classification, reduced functional status, history of dyspnoea, and need for intraoperative transfusion were risk factors associated with the occurrence of overall complications, serious complications and postoperative mortality. CONCLUSIONS: This study shows that age among other factors is a determinant of postoperative morbidity and mortality following PD.